Reviews of Environmental Contamination and Toxicology Volume 212 - Whitacre, David M.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
CONTENTS Foreword PrefaceBiochemical Effects Induced by the Hexachlorocyclohexanes Jesus Olivero-Verbal, Angélica Guerrero-Castilla, and Niradiz Reyes Ramos The Use of Cholinesterases in Ecotoxicology Bruno Nunes Tropospheric Ozone and Plants: Absorption, Responses and Consequences Kyoungwon Cho, Supriya Tiwan, S.B. Agrawal, N.L. Torres, Madhoolika Agrawal, Abhijit Sarkar, Junko Shibato, Ganesh K. Agrawal, Akihiro Kubo, and Randeep Rakwal Strategies for Decolorization and Detoxification of Pulp and Paper Mill Effluent Satyendra K. Garg and Manikant Tripathi
Foreword -- Preface -- Biochemical Effects Induced by the Hexachlorocyclohexanes -- The Use of Cholinesterases in Ecotoxicology -- Tropospheric Ozone and Plants: Absorption, Responses and Consequences -- Strategies for Decolorization and Detoxification of Pulp and Paper Mill Effluent -- Index.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Waste disposal; Environment; Ecotoxicology; Environmental Management; Waste Management/Waste Technology